Science Communication - Dascal, Marcelo; Gloning, Thomas; Leßmöllmann, Annette (Handbooks of Communication Science [HoCS] ;, 2019)
Table of contents Annette Leßmöllmann and Thomas GloningPreface - V Annette Leßmöllmann and Thomas GloningIntroduction to the volume - XI I Perspectives of research on scholarly and sciencecommunication Gregor Betz and David Lanius1 Philosophy of science for science communication in twenty-two questions - 3 Friederike Hendriks and Dorothe Kienhues2 Science understanding between scientific literacy and trust: contributions frompsychological and educational research - 29 Hans-Jürgen Bucher3 The contribution of media studies to the understanding of science communication - 51 Mike S. Schäfer, Sabrina H. Kessler and Birte Fähnrich4 Analyzing science communication through the lens of communication science:Reviewing the empirical evidence - 77 Hannah Schmid-Petri and Moritz Bürger5 Modeling science communication: from linear to more complex models - 105 Gábor Á. Zemplén6 The contribution of laboratory studies, science studies and Science and Technology Studies (STS) to the understanding of scientific communication - 123 Nina Janich7 The contribution of linguistics and semiotics to the understandingof science communication - 143 Britt-Marie Schuster8 The contribution of terminology research to the understanding of science communication - 167 Thorsten Pohl9 The study of student academic writing - 187 II Text types, media, and practices of science communication Thomas Gloning10 Epistemic genres - 209 Luc Pauwels11 On the nature and role of visual representations in knowledge productionand science communication - 235 Henning Lobin12 The lecture and the presentation - rhetorics and technology - 257 Sylvia Jaworska13 Spoken language in science and the humanities - 271 Gerd Fritz14 Scholarly reviewing - 289 Gerd Fritz15 Scientific controversies - 311 Thomas Gloning16 Symbolic notation in scientific communication: a panorama - 335 Michel Serfati †17 The rise of symbolic notation in scientific communication: the case of mathematics - 357 Benedetto Lepori and Sara Greco18 Grant proposal writing as a dialogic process - 377 III Science, scientists, and the public Wolf-Andreas Liebert19 Communicative strategies of popularization of science(including science exhibitions, museums, magazines) - 399 Sharon Dunwoody20 Science journalism - 417 Holger Wormer21 Teaching science journalism as a blueprint for future journalism education - 439 Charlotte Autzen and Emma Weitkamp22 Science communication and public relations: beyond borders - 465 Philipp Schrögel and Christian Humm23 Science communication, advising, and advocacy in public debates - 485 Philipp Niemann, Laura Bittner, Christiane Hauser and Philipp Schrögel24 Forms of science presentations in public settings - 515 IV Historical perspectives on science communication Thomas Gloning25 Historical perspectives on internal scientific communication - 547 Michael Prinz26 Academic teaching: the lecture and the disputation in the history of erudition and science - 569 Monika Hanauska27 Historical aspects of external science communication - 585 V Science communication: present and future Martina Franzen28 Reconfigurations of science communication research in the digital age - 603 Peter Reuter and Andreas Brandtner29 The library in a changing world of scientific communication - 625 Mareike König30 Scholarly communication in social media - 639 Annette Leßmöllmann31 Current trends and future visions of (research on) science communication - 657